Knowledge, Attitude, and Practices (KAPs) of Type 2 Diabetes Patients Regarding the Consumption of Artificial Sweeteners in Zahedan, Iran: A Cross-sectional Study - Mansour Karajibani; Hadi Eslahi; Farzaneh Montazerifar; Fatemeh Razaghee; Alireza Dashipour (Baqiyatallah University of Medical Sciences, 2020)
Background: Knowledge and attitude are the main indicators of awareness about the use of artificial sweeteners. Objectives: This study aimed to evaluate the knowledge, attitude, and practices (KAPs) of patients with type 2 diabetes mellitus (T2DM) in relation to the consumption of low-calorie artificial sweeteners. Methods: In this descriptive-analytical study, 400 diabetic patients admitted to the diabetes clinic of Bu-Ali hospital in Zahedan were selected by the census method. After recording the demographic characteristics, we assessed participants' knowledge and attitude through a researcher-made questionnaire. Also, the subjects' practices were evaluated based on their nutritional behaviors. The answers were marked as good, moderate, and poor. Results: The knowledge and attitude of the study population were 39% and 34.8%, respectively at the 'poor' level, 58% and 58.3% at the 'moderate' level, and 3% and 7% at the 'good' level. There was a significant relationship between patients' knowledge, attitude and their demographic indicators (p <0.001). Moreover, 8% of patients reported side effects after taking artificial sweeteners, and 20.2% of patients used artificial sweeteners in their pure form beside food. Conclusion: The findings showed that half of the diabetic patients had moderate knowledge and attitude concerning the consumption of artificial sweeteners. They had limited information about low-calorie sweeteners, which affected their nutritional behaviors so that almost half of the subjects did not consume any sweeteners. It has been suggested that appropriate educational programs be designed and implemented to overcome this information gap.